Editor’s Note - Isa, Che Ruhana; Chan, Wai Meng; Mohd Salleh, Noor Akma (Asian Journal of Business and Accounting, 2015)
It is our pleasure to present the first issue of Volume 8 of the Asian Journal of Business and Accounting (AJBA). Since indexation by Scopus in 2012, we have witnessed a tremendous progress in AJBA as can be seen from the remarkable increase in paper submission both from local and foreign scholars. In ensuring the quality of the journal, papers are subjected to a rigorous reviewing process. We thank past and present area editors as well as reviewers who have relentlessly worked towards making AJBA a success. This issue contains seven papers authored by researchers from Saudi Arabia, Qatar, Thailand, United Kingdom, Iran and Australia as well as Malaysia. Some of the papers convey the findings of collaboration between researchers from different countries. The themes of the papers range from pricing of corporate bonds and debts to corporate governance issues such as disclosure, accounting standards as well as audit fees and quality. In addition, we have also selected papers which propose direction for policy initiatives in the area of sustainability vis-Ã -vis reverse logistics and taxation. The first paper by Rahman, Omar, and Kassim, was selected from papers presented at the 16th Malaysian Finance Association Conference that was co-organised by the Faculty of Business and Accountancy, University of Malaya. Malaysia is seeing a rapid growth of the bond market thus, it is timely that Rahman et al. examine an issue pertinent to the pricing of corporate bonds. They find evidence of strong time-varying conditional variance of the Malaysian bond credit spreads with the expectation of future rate being the main determinant for credit spreads. Past news or shocks and forecast variance are also important in explaining the volatility of the spreads. The next paper by Saker, Aldamen, Abouelhemdiat and Hassira examines the impact of information risk on the costs of debts incurred by companies in Qatar. The study finds that that there is a positive relationship between discretionary accruals and the cost of debt. The findings suggest that management uses discretionary accruals opportunistically to signal information about the company. It is important that financial institutions practice good corporate governance (CG) so as to ensure sustainability. In the third paper, Sulaiman, Majid and Arifin argue that the board members of a Shariah compliant organisation are khalifah and disclosing CG is part of their accountability which aims at fulfilling their obligations to God and the broader community. Sulaiman et al. develop a CG disclosure index to assess the levels of CG disclosures in the annual reports of Islamic financial institutions (IFIs) in Malaysia. Sulaiman et al. find that the IFIs focus more on general CG information as compared to specific CG information pertaining to Shariah governance aspects. In addition, the study finds that the level of CG information disclosure by locally owned IFIs is higher than that of foreign owned IFIs. In the fourth paper, Benyarisawat, Dixon, Kaewphap and Virunjanya exploit the unique Thai accounting practice whereby listed firms are required to use both equity and cost methods to report their investments in associates. Benyarisawat et al. find that earnings information derived from the equity method is of higher value and more useful to users of the financial statements. Their findings also reveal that the cost method provides opportunities to firms to manage their earnings and thus, does not promote good corporate governance. The role played by auditors in corporate governance is undeniable. In their paper, Mohammad Rezaei, Mohd-Saleh and Ali discuss the Iranian experience following audit privatisation. They find that the effect of a sudden surge of competition coupled with the unfavourable audit market of low demand for quality audit services and litigation risks can result in unfavourable consequences. Their study shows indications of price competition and increased opportunistic auditor switching. The next paper by Abdullah and Yaakub examines the factors influencing the level of reverse logistics adoption among manufacturers located in the Northern states and the Klang Valley of Malaysia. Reverse logistics not only increase profit margins of firms but also protect the environment. Of the four factors of customer/stakeholder pressure, financial and competitive pressure, regulatory pressure and corporate citizenship pressure, the authors find that regulatory pressure has a significant strong influence on the level of reverse logistics adoption. This suggests that regulations and stringent enforcement are crucial when initiating policies to protect the environment. The final paper by Nair and Devi is timely in view of the current raging discussion on taxation policies in Malaysia. The paper debates on the issue of tax reliefs conferred on caregivers of disabled family members. Malaysian taxation policies grant tax reliefs only to caregivers of disabled parents, spouse and child unlike the position taken in Singapore and Thailand where similar benefits are extended to sibling caregivers. Using the autoethnography approach, Nair and Devi explain the need to review this tax policy in Malaysia. Further, the revision might be necessary so as to synchronise with the tax policies of other members in the ASEAN Economic Community (AEC). We wish to record our appreciation to the Malaysian Accountancy Research and Education Foundation (MAREF) for their financial support. We hope this issue brings AJBA closer to achieving its mission which is to incrementally provide a voice for scholars embarking on Asia-focused research.